2020
DOI: 10.1590/0100-6991e-20202510
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of difficulty in bedside percutaneous dilatational tracheostomy: pilot study

Abstract: Introduction: percutaneous dilatational tracheostomy is currently one of the main procedures performed in an intensive care unit (ICU). However, there are no well-defined indicators of technical difficulty in performing the procedure. Objectives: to define predictors of difficulty in performing bedside percutaneous dilatational tracheostomy. Methodology: prospective cohort study encompassing 21 patients who underwent bedside percutaneous dilatational tracheostomy in the ICU at a single center. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
1
0
3
Order By: Relevance
“…Before the pandemic, PDT was the standard procedure for tracheostomies in the ICU. 10 Our study has found that PDTs still can be safely performed at the bedside of COVID‐19 patients in ICU. Performing PDTs in the ICU is safe for two reasons.…”
Section: Discussionmentioning
confidence: 71%
“…Before the pandemic, PDT was the standard procedure for tracheostomies in the ICU. 10 Our study has found that PDTs still can be safely performed at the bedside of COVID‐19 patients in ICU. Performing PDTs in the ICU is safe for two reasons.…”
Section: Discussionmentioning
confidence: 71%
“…Estancia en el hospital y en la UCI: en su estudio Dochi et al (37), demostraron una duración más corta entre la TQ temprana y tardía en cuanto a la estadía en el hospital (TQ temprana vs TQ tardía; 49 IQR [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] vs 70 IQR [62-78]; p: .01) como también la estadía en la UCI (TQ temprana vs TQ tardía; 13 IQR [11][12][13][14][15][16] vs 20 IQR [17][18][19][20][21][22][23]; p: .002). Igualmente, Puentes et al (43), especifican en su estudio que los tiempos de estadía en el hospital (TQ temprana vs TQ tardía; 37,5 vs 57,6; p: <.001) y en UCI (TQ temprana vs TQ tardía; 21,5 vs 36,9; p: <.001) tuvieron significancia estadística.…”
Section: Tiempo De Intubación Endotraquealunclassified
“…Estudios a nivel mundial describen que la TQ está presente en el 10,7% de los pacientes con ventilación mecánica (VM) ingresados en la unidad de cuidados intensivos (UCI) (1,5,(7)(8)(9). La TQ se realiza tras una valoración en donde se pronostica un destete prolongado y dificultoso tras una intubación endotraqueal (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionunclassified
See 1 more Smart Citation